The broken brain the biological revolution in psychiatry - Andreasen, Nancy C. (New York Harper & Row, 1984)
Details recent advances in neuroscience that have yielded a more accurate understanding of the brain's functions and malfunctions and, in turn, have moved psychiatry away from psychotherapy and into the mainstream biological traditions of medicine.
Includes index.
Keywords: Mental illness -- Physiological aspects; Neuropsychiatry; Mental Disorders -- Physiology